Evaluation of Verification of Political Parties Participating in the 2024 General Election - Sultan, Wabil Fadli; Sukri; Yunus, Ariana (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
The verification stage is the process of checking the completeness and validity of the registered political party documents. This stage has been carried out by the KPU since July 2022 and will continue until December 2022. In this verification process, it is necessary to evaluate the implementation of existing regulations in order to realize better election governance in Indonesia. The research to be carried out is a qualitative field research. The results of the study indicate that there are still several obstacles in carrying out the verification of eligible participants. First, the use of the SIPOL application in the registration process still often results in errors that slow down the ongoing registration process. Second, there is a stigma that election organizers are unfair because they provide more space for parliamentary parties. Third, the same violations still occurred in the previous election, namely violations in cases of profiteering people's names as members or administrators of political parties.